MEDIATION EXISTENCE CRIMINAL PENAL SETTLEMENT - Erma Rusdiana (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2018)
Indonesian Constitution states that all people of Indonesia are entitled to equal treatment before the law as stated in Article 28 D, paragraph 1 of the 1945 Constitution, but they are not always easily access it. The principle of justice is simple, fast and low cost can’t be reached by most people. Currently, there is also a change and dynamics of complex societies and regulations in some legislation. It also has implications on the public nature of the criminal law has shifted its relative entered the private sphere with known and practiced penal mediation. Issues raised in this paper is the concept of criminal law enforcement based on the existence of pluralistic and penal mediation as an alternative solution-in the practice of the criminal settlement. Of the studies that have been done that the concept of legal pluralism is no longer emphasizes the dichotomy between the legal system of the state on the one hand with the legal system of the people folk law and religious law on the other side. That law enforcement-based pluralistic more emphasis on interaction and co-existence of the workings of the various legal systems that affect the operation of norms, processes and institutions in masyarakat.Polarisasi law and penal mediation mechanisms can do, as long as it is earnestly desired by all parties ( suspects and victims), as well as to reach a wider interest, namely the maintenance of social harmony. In summary penal mediation would have positive implications philosophically that achieved justice done fast, simple and inexpensive because the parties involved are relatively small compared through the judicial process with the components of the Criminal Justice System